1995
DOI: 10.1109/9.400474
|View full text |Cite
|
Sign up to set email alerts
|

Absolute stability in linear delay-differential systems: ill-posedness and robustness

Abstract: of f~~ ( s ) in the closed right half plane {Re ( 8 ) 2 0). The system ($1 is said to be stable independent of delay (i.0.d.) if it is asymptotically stable for every /I E H . In this case we say that the system is Example 2.1: Consider the delay-differential system (*) s'(t) = James Louisell absolutely stable. -x ( t ) -~( t h ) -0.5:r(t -2h). the system used by Datko [41Abs~cl-Tbeaulhorconsidersmatrlxdelay-di~eranUaIsyste~which as an example,the while is simply the delay operator acting on scalar function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…the closed-loop system becomes of neutral type. The instability caused by such a small delay in the loop has been studied for a various kind of systems (see e.g., Barman et al 1973;Datko 1988;Louisell 1995). Owing to the improved tool of Logemann et al (1996), we know that the neutral system is practically stable if à is Schur.…”
Section: Dynamic Controllersmentioning
confidence: 99%
“…the closed-loop system becomes of neutral type. The instability caused by such a small delay in the loop has been studied for a various kind of systems (see e.g., Barman et al 1973;Datko 1988;Louisell 1995). Owing to the improved tool of Logemann et al (1996), we know that the neutral system is practically stable if à is Schur.…”
Section: Dynamic Controllersmentioning
confidence: 99%
“…We first give a simple example in which the derivative feedback stabilizes, whereas its difference approximation can not for all small Ì . Such ill-posedness may be compared to known instability caused by introducing small time-delays in the feedback loop (see e.g., Datko 1988;Louisell 1995;Longemann and Townley 1996).…”
Section: Application Of the Criterionmentioning
confidence: 99%
“…In [15] it is shown that delay-independent stability is equivalent to asymptotic stability for all delay values lying in a nontrivial sector in the delayparameter space, and to the robustness of stability of a ray, consisting of commensurate delay values, w.r.t. small perturbations of the direction (see [15] for precise formulations). Note that the latter two statements imply the existence of a stable ray, which is not subjected to the interference phenomenon.…”
Section: {0}) Then There Exist Delay Values For Which (11) Has Charmentioning
confidence: 99%
“…A further example (scalar system including two delays) of delay interference can be found in [5]. This is also discussed in [15] and [22], where some characterizations regarding interference are given (a frequency-sweeping test combined with a matrix pencil condition in [22], a sector characterization in [15]). As we shall discuss at the end of Section 5, these results appear as corollaries of the general theory developed throughout the paper.…”
mentioning
confidence: 99%
See 1 more Smart Citation